Applied Aspects of Public Administration in the Field of Environmental Protection: Innovative Approaches to Implementing Digital Mechanisms on the Basis of Public-Private Partnership - Lazorenko, L. V.; Vorobyov, S. V. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2025)
This article examines a set of problems that arise during the digitalization of the processes for implementing the control functions of civil society institutions and state authorities in Ukraine’s environmental protection sector. It is shown that instability of the regulatory and legal environment, ongoing organizational transformations, and an increasing number of environmental challenges create the need for dynamic adaptation of digital mechanisms for public oversight. The paper substantiates the importance of creating a unified information and communication infrastructure for environmental protection by integrating existing and prospective instruments for state–public interaction. It is determined that the effectiveness of such instruments largely depends on the quality of software algorithm design, their coherence, scalability, and resilience to change. Special attention is paid to the economic aspects of adapting software algorithms, in particular the risks of underestimating or overestimating the costs of redesign and reengineering work. The absence in Ukraine of a unified methodology for preliminary cost estimation of the development and modernization of digital products is emphasized; this complicates planning and increases the likelihood of inefficient use of budgetary resources. It is demonstrated that taking into account economic, technological, and regulatory factors is a key precondition for the sustainable functioning of digital solutions in the field of public oversight. Based on the analysis, the paper argues for the advisability of applying a systems approach in the development and legal provision of digital mechanisms for public oversight. The conclusion is drawn that the digital transformation of the environmental protection sector should be regarded as a tool for improving the quality of public administration and for engaging the public, rather than as an end in itself. The importance of the continuity of state strategic investments in digital technologies is stressed, since any slowdown creates risks of technological lag and reduced effectiveness of authorities’ activities.